Mary Anne saves the day - Martin, Ann M. 1955- (New York Scholastic, 2020)
When a fight breaks out among the members of the Baby-sitters Club, timid Mary Anne finds herself becoming more assertive as a baby sitter and in her relationships with her father and friends.
3.7
4-7
Keywords: Babysitters -- Fiction; Friendship -- Fiction; Assertiveness (Psychology) -- Fiction; Realistic fiction